Demographics and the Irony of Existential Profiling in Yorùbá Thought: Policy Considerations for Nigeria - Wale Olajide (Yoruba Studies Review)
This essay interrogates what can be described as Yorùbá population philosophy, within the context of Yorùbá existential thought, and the effects it has on Nigeria’s population explosion. The essay explores the seemingly contradictory proverbs that both vindicate and vilify the act of giving birth to many children. The essay further connects this traditional Yorùbá wisdom to contemporary procreative practices of Yorùbá Christians and Muslims, and their interpretations of scriptural injunction to be fruitful and multiply. I then argue that if Nigeria’s lackluster policy on population is taken into consideration, the implications of the Yorùbá, as well as other ethnic groups’, population philosophy will not only aggravate the Nigerian postcolonial predicament, but will eventually explode the population time bomb already ticking in Nigeria. The essay recommends that given the existential complexities attached to giving birth to a child, together with the demographic exigencies on Nigeria’s national predicament, marriage ought to be strictly regulated and limited to those with the capacity for sustainability.